Raios e precipitações na Amazônia Oriental: efeitos no sistema elétrico - SANTOS, Ana Paula Paes dos (2019)
This work analyzes the atmospheric discharge occurrences, in local and large scale, over the eastern Amazon Region, during the 2006 to 2009 period. In the local scale, the relations between precipitation and lightning density of occurrences observed daily by the SIPAM’s LDN were considered, during a rainy and a dry quarters, over an area of 900 km² which encloses the city of Belém-PA. The smoothed data, obtained through seven day averages filtering, showed good correlation between lightning density and precipitation during the rainy period. During the dry quarter, intense lightning storms were observed, with no apparent quantitative relation to the local daily precipitation averages. A regression between these two variables was derived and presented, for the rainy quarter. The differences between the seasonal behaviors of lightning frequency of occurrences versus rainfall were attributed to the differences of coverage between meso and large scale meteorological systems which produce lightning and rainfall over this region. In order to exemplify such distinctions, lightning density of occurrences maps were presented, for weeks of each period. It was possible to conclude that, during the rainy period, one may estimate the regional precipitation from the lightning frequency of occurrences data. A large scale study was made considering the possible relations between the power outages attributed to lightning of regional electric energy distribution systems belonging to CELPA Rede Energia and sea surface temperatures (SST) anomalies on the Pacific and Atlantic Oceans. The results showed that, with some time gaps, the number of power disruptions presented a tendency to follow the lightning occurrence density variations. Additionall evidence indicated that, the power outage increments on the eastern Amazonian electrical systems were closely associated to negative SST anomalies over the equatorial Pacific Ocean.